2014
DOI: 10.1186/1472-684x-13-29
|View full text |Cite
|
Sign up to set email alerts
|

Home telehealth and paediatric palliative care: clinician perceptions of what is stopping us?

Abstract: BackgroundAdvances in technology have made the use of telehealth in the home setting a feasible option for palliative care clinicians to provide clinical care and support. However, despite being widely available and accessible, telehealth has still not been widely adopted either in Australia or internationally. The study aim was to investigate the barriers, enablers and perceived usefulness for an established home telehealth program in paediatric palliative care from the perspective of clinicians.MethodsSemi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(136 citation statements)
references
References 21 publications
2
132
0
2
Order By: Relevance
“…In fact, through a collaborative approach and integration of multiple perspectives, a patient's plan of care becomes individualized and a reductionist approach is avoided. [4,13,19] Empowered caring illuminates that without empirical knowing, depth, and breadth of knowledge, critical thinking and advanced skills would not be possible. Technology and equipment are just tools that assist nurses in their work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, through a collaborative approach and integration of multiple perspectives, a patient's plan of care becomes individualized and a reductionist approach is avoided. [4,13,19] Empowered caring illuminates that without empirical knowing, depth, and breadth of knowledge, critical thinking and advanced skills would not be possible. Technology and equipment are just tools that assist nurses in their work.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] This further hinders a nurse's ability to establish a therapeutic relationship, resulting in nurses distancing themselves, losing physical proximity [12] and nurse presence. [4,13] A biomedical model continues to influence patient care because emphasis is placed on evidence-based practice with measurable outcomes; ultimately, resembling an audit culture with the undertone of a business model. [14][15][16] Nurses should never be reluctant to integrate a biomedical model or technology into practice because this affords nurses the opportunity to expand critical thinking and problem-solving abilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tele-hospice was able to decrease spiritual and medical burden, improving quality of life and symptom management for veterans and families coping with end of life [114]. Home tele-health consultations are a feasible and acceptable means of facilitating a palliative care consultation reducing the burden on families also in paediatric patients [115,116].…”
Section: Role Of Tele-monitoring In Sleep-related Breathing Disordersmentioning
confidence: 99%
“…For example, in health care, online consultations have been studied to understand how a customer's lack of trust decreases their potential to engage in "…exchanges that require divulging sensitive information, such as health issues" (Gummerus, Liljander, Pura and van Riel, 2004, p. 175). A recent quantitative study by Russell, Gillespie, Hartley, Theodoros, Hill and Gray (2015) found that trust in telehealth was the strongest predictor of customer uptake of telehealth in the home for aged patients and is salient to providers' telehealth use (Bradford, Caffery and Smith, 2015;Bradford, Young, Armfield, Herbert, and Smith (2014). Radhakrishnan, Jacelon and Roche (2014) found in interviews with 40 nurses that trust in technology equipment accuracy drove acceptance.…”
Section: Problematising Service Separation and Trust: The Case Of Telmentioning
confidence: 99%